Potent VEGF blockade causes regression of coopted vessels in a model of neuroblastoma - Kim, Eugene S. (National Academy of Sciences, 2002)
Vascular endothelial growth factor (VEGF) plays a key role in human tumor angiogenesis. We compared the effects of inhibitors of VEGF with different specificities in a xenograft model of neuroblastoma. Cultured human neuroblastoma NGP-GFP cells were implanted intrarenally in nude mice. Three anti-VEGF agents were tested: an anti-human VEGF(165) RNA-based fluoropyrimidine aptamer; a monoclonal anti-human VEGF antibody; and VEGF-Trap, a composite decoy receptor based on VEGFR-1 and VEGFR-2 fused to an Fc segment of IgG1. A wide range of efficacy was observed, with high-dose VEGF-Trap causing the greatest inhibition of tumor growth (81% compared with controls). We examined tumor angiogenesis and found that early in tumor formation, cooption of host vasculature occurs. We postulate that this coopted vasculature serves as a source of blood supply during the initial phase of tumor growth. Subsequently, control tumors undergo vigorous growth and remodeling of vascular networks, which results in disappearance of the coopted vessels. However, if VEGF function is blocked, cooption of host vessels may persist. Persistent cooption, therefore, may represent a novel mechanism by which neuroblastoma can partly evade antiangiogenic therapy and may explain why experimental neuroblastoma is less susceptible to VEGF blockade than a parallel model of Wilms tumor. However, more effective VEGF blockade, as achieved by high doses of VEGF-Trap, can lead to regression of coopted vascular structures. These results demonstrate that cooption of host vasculature is an early event in tumor formation, and that persistence of this effect is related to the degree of blockade of VEGF activity.